Perancangan Animasi Gatotkaca Sebagai Media Edukasi Makanan Ultra-Proses Menggunakan Metode Design Thinking - Pratiwi, Diana Hakim; Adi Kurniawan, Rendya; Muslihah, Isnawati; Rachman, Anung (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
Ultra-processed food (UPF) is increasingly dominating dietary patterns despite its well-documented negative health impacts. The low level of public awareness about the dangers of UPF highlights the need for educational efforts that are both effective and engaging, especially for teenagers and young adults. This study aims to develop the Gatotkaca character design as an educational medium for ultra-processed foods within an educational animation context. Gatotkaca was chosen due to his strong cultural and heroic image, which are expected to resonate with the target audience. The study uses a qualitative descriptive approach and adopts the design thinking method, consisting of empathize, define, ideate, prototype, and test. Data were collected through direct observation (primary source) and literature studies (secondary source). The findings indicate that visual media such as animation has strong potential in conveying health education, particularly regarding UPF. The animated video is expected to serve as an informative, entertaining, and emotionally engaging educational tool. This design offers a fresh approach by combining modern visual storytelling with cultural elements